Aesthetics of Emotions: Between Phenomenology and Pragmatism (Itinera, 2018)
This paper aims to investigate the nature of aesthetic experience, focusing on the interplay between emotions and cognition. We shall establish a link between a phenomenological account of emotions and a pragmatist, anti-dogmatic view on aesthetics, such as that defended by John Dewey. Although pragmatism and phenomenology have historically emerged as separate traditions, they might mutually share resources to achieve an exhaustive description of aesthetic experience. Both traditions conceive aesthetics as a “philosophy of experience”, and they agree on the decisive role emotional intentionality plays in the constitution of an aesthetic experience.